Opportunity and Worker Commitment in Oil Servicing Companies in Bayelsa State, Nigeria - , Joy Chidiebere Nwaiwu; Lucky Ajor , (IJRDO - Journal of Applied Management Science, 2020)
This study adopted descriptive statistics design and covered a population of 1400 workers of oil servicing companies in Bayelsa State, Nigeria. Data was generated through a five point Likert scale questionnaire designed and the formulated researches Hypotheses were tested using the Spearman’s Rank Order Correlation Coefficient statistical tool. The outcome of the test revealed that there are significant relationships between opportunity and the measures of worker commitment (affective commitment, normative commitment and continuance commitment).with the aid of the SPSS version (21.0) of statistical package for social sciences. The conclusion was drawn on the fact that organizations should begin to identify opportunity/career development beyond just once event or an act to incentivize employees. They should see it as a continuous process and a strategic activity of the human resource department that can ensure the attainment of both the economic and psycho-social needs of the employees with the profit and sustainable goals of the organization.